Corpus callosum tissue loss and development of motor and global cognitive impairment: the LADIS study - Frederiksen, Kristian Steen; Garde, Ellen; Skimminge, Arnold; Barkhof, Frederik; Scheltens, Philip; Straaten, Elisabeth C. W. van; Fazekas, Franz; Bäzner, Hansjörg; Verdelho, Ana; Ferro, José M.; Erkinjuntti, Timo; Jokinen, Hanna; et al. (Dementia and geriatric cognitive disorders, 2012)
Objective: To examine the impact of corpus callosum (CC) tissue loss on the development of global cognitive and motor impairment in the elderly. Methods: This study was based on the Leukoaraiosis and Disability (LADIS) study. Assessment of cognitive and motor functions and magnetic resonance imaging (MRI) were done at baseline and at a 3-year follow-up in nondemented elderly subjects. Results: 328 of 639 LADIS subjects had MRIs at baseline and at the 3-year follow-up, which allowed for assessment of CC. Logistic regression revealed differential tissue loss rates in posterior CC in subjects converting to dementia, compared to nonconverters (p < 0.05). Anterior and posterior CC tissue loss was significantly correlated with self-perceived memory impairment in nonconverters (p < 0.05). CC tissue loss was also significantly associated with impaired single leg stance time (p < 0.01). Conclusion: The present longitudinal study on CC supports the role of callosal tissue loss in the development of global cognitive as well as motor impairment.